Finding NEMO: Documentation of the Norwegian Economy Model - Leif Brubakk; Tore Anders Husebø; Junior Maih; Kjetil Olsen; Magne Østnor (Norges Bank, 2006)
Over the last decade monetary policy in Norway has gradually evolved from exchange rate targeting to flexible inflation targeting. In addition, globalization has affected the Norwegian economy substantially over the last decade. Monetary policy has increasingly been challenged on how to respond to supply side shocks, including shocks to productivity, the degree of competition both in product and labour markets,and terms of trade shocks. With all these developments came the need for new modeling tools. In this paper we document a new open-economy model for Norway named NEMO, that has been developed at Norges Bank as a tool for forecasting and policy analysis under the new monetary policy regime. In addition to a full technical account and description of the model properties, we explain the motivation and the modeling approaches that have been used, including the parameterization.
hdl:11250/2508017
Keywords: 330